TRANSLATION OF KOREAN-INDONESIAN SHORT STORIES: AN ANALYSIS OF CLASS AND SEMANTIC SHIFTS OF ADVERBS OF MODALITY - Syahbaniyah, Nur Rosyidah; Suhardijanto, Totok (LiNGUA: Jurnal Ilmu Bahasa dan Sastra, 2021)
This study discusses class and semantic shifts of adverbs of modality in the Korean short story and its Bahasa Indonesia translation in the short story anthology of ‘Langit dan Kupu-Kupu. This study aims to identify how the adverbs of modality original text change into a different word class in the target text. The sources of data in this study were six Korean short stories entitled ‘Dua Generasi yang Teraniaya’, ‘Seoul Musim Dingin 1964’, ‘Jalan ke Sampho’, ‘Bung Kim di Kampung Kami’, ‘Dinihari ke Garis Depan’, dan ‘Betulkah? Saya Jerapah’ and its Indonesian translation. This study was conducted using a descriptive qualitative method, and the design of a linguistic corpus was used to collect analytical data. The analysis results found that from 46 adverbs of modality, four translated adverbs remained classified as adverbs. At the same time, the other ten words change their class into pronouns, nouns, particles, adjectives, and verbs. Additionally, the other 32 words have a combination of adverbs and other word classes. Furthermore, of the 290 adverb words in the source text, 143 words were accurately translated, 100 were deleted, and 47 changed their meaning in the TT. In the translation of Korean-Indonesian short stories, the shifting technique is used to adjust differences between Korean and Indonesian grammar systems. Translators also make a shift in the word's meaning of short stories as long as they do not deviate from the context and message in the ST to produce a natural translation that TL readers can easily understand.